Tumor Necrosis Factor Receptor Superfamily, Member 1B Haplotypes Increase or Decrease the Risk of Inflammatory Bowel Diseases in a New Zealand Caucasian Population. (17th March 2009) - Ferguson, Lynnette R.; Han, Dug Yeo; Huebner, Claudia; Petermann, Ivonne; Barclay, Murray L.; Gearry, Richard B.; McCulloch, Alan; Demmers, Pieter S.
Abstract : Inflammatory bowel diseases (IBDs) comprising Crohn disease (CD) and ulcerative colitis (UC) are chronic inflammatory conditions with polygenic susceptibility. Interactions between TNF-alpha and TNF-alpha receptor play a fundamental role in inflammatory response. This study investigates the role that selected single nucleotide polymorphisms (SNPs) and haplotypes in the TNF-alpha receptor (TNSFRSF1B) gene play in the risk of IBD in a New Zealand Caucasian population. DNA samples from 388 CD, 405 UC, 27 indeterminate colitis patients, and 293 randomly selected controls, from Canterbury, New Zealand were screened for 3 common SNPs in TNSFRSF1B: rs1061622 (c .676 T > C ), rs1061624 (c . ∗ 1663 A > G ), and rs3397 (c . ∗ 1690T > C ), using TaqMan technologies. Carrying the rs1061624 variant decreased the risk of UC in the left colon (OR 0.73, 95% CI = 0.54 –1.00) and of being a smoker at diagnosis (OR 0.62; 95% CI = 0.40 –0.96). Carrying the rs3397 variant decreased the risk of penetrating CD (OR 0.62, 95% CI = 0.40 –0.95). Three marker haplotype analyses revealed highly significant differences between CD patients and control subjects (χ 2 = 29.9, df = 7, P = .0001 ) and UC cases and controls (χ 2 = 46.3, df = 7, P < .0001 ). We conclude that carrying a 3-marker haplotype in the TNSFRSF1B gene may increase (e.g., haplotype of GGC was 2.9-fold more in the CD or UCpatients) or decrease (e.g., TGT was 0.47-fold less in UC patients) the risk of IBD in a New Zealand Caucasian population.